Cardiac calcium handling on trial: editorial - Pleger, Sven Torsten; Raake, Philip; Katus, Hugo; Most, Patrick (Circulation research, 2014)
Targeting abnormal calcium (Ca)2+ handling in ventricular cardiomyocytes emerged as a new paradigm for human heart failure (HF) therapy.1 Cardiomyocytes come with an extensive Ca2+ signaling toolkit consisting of various Ca2+ transporters, Ca2+ channels, Ca2+ buffer, and sensor proteins. Organized into self-contained signaling modules in which Ca2+ signaling functions within highly localized environments, the cardiac Ca2+ signalosome delivers dynamic signals with different spatial and temporal properties that relay compartmentalized Ca2+ oscillations into specific cellular functions.2 As a result, Ca2+ governs not only the cardiomyocyte contractile cycle, but also concurrently control transcription and muscle growth, electric excitability, cell survival, and energy metabolism.3 Article, see p 101. Key components of the cardiac Ca2+ signalosome remodel as a molecular hallmark in HF: loss of sarco(endo)plasmic reticulum ATPase 2a (SERCA2a) expression surfaced as 1 critical abnormality in experimental HF and human failing myocardium. The defect alone is sufficient to disable various Ca2+-dependent homeostatic mechanisms that drive further deterioration of cardiac function and structure after a primary insult, such as myocardial infarction.1 Translational studies, particularly in human-relevant large animal models, have successfully used recombinant adeno-associated viral (rAAV) vectors for cardiac- targeted delivery of therapeutically formulated synthetic SERCA2a DNA that resulted in safe and long-term restoration of cardiac function and reversal of structural, electric, and metabolic remodeling in experimental HF.4 Hence, targeting defective components of the cardiomyocyte Ca2+ signalosome in HF might bear therapeutic benefits beyond sole improvement of cardiac contractile performance (Figure). Figure. Calcium (Ca)2+ regulation of cardiomyocyte function is not limited to contractile performance but extends to control over nuclear transcription, electric activity, cell survival, and energy metabolism . …